Synthesis, Crystal Structure Refinement, and Electrical Conductivity of Pb(8−x)Na2Smx(VO4)6O(x/2) - Tatiana M. Savankova; Lev G. Akselrud; Lyudmyla I. Ardanova; Alexey V. Ignatov; Eugeni I. Get’man; Roman E. Gladyshevskii; Stanislav N. Loboda (Journal of Chemistry)
Solid solutions of Pb(8−x)Na2Smx(VO4)6O(x/2) were studied using X-ray diffraction analysis including Rietveld refinement and scanning electron microscopy and by measuring their electrical conductivity. Crystal structure of the solid solutions was refined and the solubility region 0≤x≤0.2 was determined for samarium substitution for lead under the scheme 2Pb2++□→2Sm3++O2-. The influence of degree of substitution on the electrical conductivity of solid solutions was established.